Answer:
x = sqrt(273)/2 - 1/2 or x = -1/2 - sqrt(273)/2
Step-by-step explanation:
Solve for x:
x - 3 = 56/(x + 4)
Cross multiply:
(x - 3) (x + 4) = 56
Expand out terms of the left hand side:
x^2 + x - 12 = 56
Add 12 to both sides:
x^2 + x = 68
Add 1/4 to both sides:
x^2 + x + 1/4 = 273/4
Write the left hand side as a square:
(x + 1/2)^2 = 273/4
Take the square root of both sides:
x + 1/2 = sqrt(273)/2 or x + 1/2 = -sqrt(273)/2
Subtract 1/2 from both sides:
x = sqrt(273)/2 - 1/2 or x + 1/2 = -sqrt(273)/2
Subtract 1/2 from both sides:
Answer: x = sqrt(273)/2 - 1/2 or x = -1/2 - sqrt(273)/2